Comparative biochemical efficacy analysis of an alpha1-proteinase inhibitor (Glassia®) in patients with alpha-1 antitrypsin deficiency. (June 2022) - Li, Zhaoyang; Franke, Ryan M.; Morris, Denise; Yel, Leman
Abstract: Alpha1 -proteinase inhibitor (A1PI) augmentation is the only specific treatment targeting the underlying deficiency in alpha1 -antitrypsin deficiency (AATD). The demonstration of efficacy has been based on maintaining the biochemical surrogate endpoints of plasma antigenic and functional A1PI levels above >11 μM. Here we report a biochemical comparability analysis based on data from a phase 2/3, randomized, double-blind, two-arm study with partial crossover of Glassia® (Baxalta US Inc. Westlake Village, CA, USA) and Prolastin® (Grifols Therapeutics LLC, Research Triangle Park, NC, USA) in patients with AATD (NCT00460096). Patients (N = 50) were randomly assigned in a 2:1 ratio to receive either Glassia (n = 33) or Prolastin (n = 17), respectively. In the present study, data from patients in the per-protocol population (n = 29, Glassia; n = 12, Prolastin) were analyzed. We compared the biochemical efficacy of these two A1PI products at steady state of A1PI in plasma after weekly intravenous administration of A1PI at a dose of 60 mg/kg body weight. For both antigenic and functional A1PI levels, with or without baseline correction, the geometric mean ratios (GMRs) of plasma trough levels (Glassia/Prolastin) over a 6-week period at steady state (Weeks 7–12 post-randomization) were near or above 100%, with the 90% confidence intervals (CIs) contained within the 80%–125% interval. For antigenic A1PI, the GMR (90% CI) was 115.8% (108.1–124.2) for baseline corrected and 114.2% (109.2–119.5) for uncorrected concentrations. For functional A1PI, the GMR (90% CI) was 98.7 (92.5–105.4) for baseline corrected and 107.8% (102.3–113.5) for uncorrected concentrations. In conclusion, the biochemical efficacy of Glassia using the endpoints of plasma antigenic and functional A1PI trough concentrations at steady state was comparable with Prolastin in patients with AATD.